Insulated Metal Sheet Roofing - Romero, Raymundo V.; Romero, Nelson V.; Romero, Fe B. (Asia Pacific Higher Education Research Journal (APHERJ), 2017)
Three models were used on study of insulating corrugated galvanized iron (GI) sheets using coconut fibers. Model 1 was with mortars and fibers. Model 2 was with mortars without fibers. Model 3 is the conventional model. Occurrence of physical defects was investigated for models 1 and 2 within the curing period. Internal temperatures were observed considering inside the bucket (IBT), carton box (ICBT), and wooden box (IWBT). Model 2 shows signs of more visible defects by which the mortar detached from the corrugated GI sheet. Compared with Model 3, the IBT, ICBT and IWBT are lower using Model 1 as top cover. Model 1 used to minimize the internal temperature of different kind and quality of boxes. Among the three containers, it is in the wooden box that the IBT, ICBT and IWBT are the lowest. The researchers recommended a similar study using model houses.